Wojna i pokój? Publicystyka rosyjskojęzyczna w przekładzie na język polski po lutym 2022 roku - Alicja Pstyga (Studia Rossica Posnaniensia)
Referring to the main theme of the conference, the author addresses the problem of translating Russian-language journalism amid the ongoing war in Ukraine. These events prompt us to perceive media messages not only within the framework of a culture entangled in politics, evoking (neo)imperial and (neo)colonial issues, but also matters of value systems and Russophobia. This situation influences the choice of topics and sources of media texts offered to Polish recipients through translation. As a foundation for a confrontational reading, the author chose Russian journalism translated into Polish, using the example of the “Forum” magazine, which features reprints from the world press and has included a Russian section since the beginning of the magazine’s existence. The analysis of the content of reprints from Russian-language media, alongside the assessment of translation solutions, attempts to answer the question about war and peace, both from the perspective of translation and the condition and prospects of Russian studies in Poland. The translation itself, often framed in terms of war, poses not only traditional translation problems related to equivalence, adequacy, and the function of translated texts but also introduces new challenges of a moral and ethical nature associated with experiencing and depicting human suffering. From the perspective of interlingual and intercultural media discourse, important research issues also emerge, such as persuasion, manipulation, and propaganda.